Satisfaction of service recipients on quality of service of the Public Health Center 50 Buengkum, Health Department, Bangkok Metropolitan Administration - Kongpom, Butsakorn pink; Atthakorn, Wiwatchai (Vajira Medical Journal : Journal of Urban Medicine, 2019)
Objectives: The main objective of this research was to study people’s satisfaction of medical services provided by Public Health Center 50, Buengkum, Health Department, Bangkok Metropolitan Administration. The indirect objectives were 1) to analyze the correlation between people’s satisfaction and other factors 2) to listen to people’s opinions and suggestions on the quality of services provided by the Public Health Center, Health Department, Bangkok Metropolitan Administration. Methods: This study was a survey research. The population was people who had received the services provided by Public Health Center 50 Buengkum, Health Department, Bangkok Metropolitan Administration. The size of sampling, 200 people, was calculated by TARO Yamane’s formula using simple random sampling method. The statistics used for data analysis were percentage, arithmetic mean, standard deviation, t - test, one - way Anova (Analysis of Variance) and LSD (Least Significant Difference). Results: The findings revealed that overall, people were very satisfied with quality of services such as the service convenience, worthwhileness, service reliability, service-minded attitude and staff’s morality, with statistically significant at = 3.83, SD = 0.184. The groups of people who were mostly satisfied were people aged 51 – 60 years and older. Suggestions: There were some suggestions for Bangkok Metropolitan Administration and policy suggestions for the relevant government agencies to improve the quality of government’s public health services.